Dimensions of hope and the school environment: Results from a school-wide needs assessment at an urban high school - James P Canfield; Wendy L Wilson; Lauren Shute; Amy N King; Kennesha J Smith; Dana Harley (International Journal of School Social Work, 2023)
Objectives: Various aspects of hope can play a major role in how students from urban locales perceive their school environment. The purpose of this study is to examine the relationships between various dimensions of hope and the school environment as perceived by adolescents at an urban high school. Methods: Data from a school-wide needs assessment measuring urban adolescents’ perceived hope and perceptions of the school environment were analyzed. Results: The analysis from regression models indicate that the dimensions of hope variables can be predicted by perceptions of the school environment. Conclusion: Overall, the urban adolescent hope domains of Spirituality, Personal Agency, Education, and Caring Connections all proved to be important elements correlated with the school environment. Implications of these findings for future research and practice are discussed
Keywords: hope; schools; school social work; school environment; school climate; urban schools; adolescence